2018
DOI: 10.7554/elife.35222
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric regulators selectively prevent Ca2+-feedback of CaV and NaV channels

Abstract: Calmodulin (CaM) serves as a pervasive regulatory subunit of CaV1, CaV2, and NaV1 channels, exploiting a functionally conserved carboxy-tail element to afford dynamic Ca2+-feedback of cellular excitability in neurons and cardiomyocytes. Yet this modularity counters functional adaptability, as global changes in ambient CaM indiscriminately alter its targets. Here, we demonstrate that two structurally unrelated proteins, SH3 and cysteine-rich domain (stac) and fibroblast growth factor homologous factors (fhf) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 120 publications
(211 reference statements)
3
52
0
Order By: Relevance
“…Interestingly, STAC proteins have recently been found to engage Ca V s (51)(52)(53)(54)(55)(56)(57) and were shown to interact with the EF-hand domain, abolishing CDI (26). This is reminiscent of the effect of FHFs on Na V s, and it was shown that FHFs can abolish CDI in Na V 1.4 (26). Although there are parallels between Na V and Ca V channels in regard to CaM regulation, there is also divergence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, STAC proteins have recently been found to engage Ca V s (51)(52)(53)(54)(55)(56)(57) and were shown to interact with the EF-hand domain, abolishing CDI (26). This is reminiscent of the effect of FHFs on Na V s, and it was shown that FHFs can abolish CDI in Na V 1.4 (26). Although there are parallels between Na V and Ca V channels in regard to CaM regulation, there is also divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FHFs have been shown to abolish CDI in Na V 1.4 (26), an effect that may be ascribed to its inherent effect on the EF-hand orientation, locking it into a position such that no Ca 2+ -dependent conformational change occurs. Similarly, STAC proteins, which can bind to two different regions in Ca V 1 channels (26,(51)(52)(53)(54)(55)(56), including the EFhand domain (26), could affect the relative orientation between EF-hand and IQ domain. How this conformational change further results in inactivation remains to be shown, but of note is the ability of the EF-hand domain to interact with the III-IV linker, and that this interaction affects channel inactivation (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the calcium-binding protein calmodulin (CaM) is a yet-unknown N-terminal interaction partner. CaM is well-known to regulate voltage-gated sodium (Na v ) and calcium (Ca v ) channel functions 2,14 . Its interaction with Na v and Ca v C-terminal domains (CTD) is especially well established 2,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Larger calcium currents may be the result of changes in voltage-dependent activation and inactivation curves of the channels to more hyperpolarized potentials, as identified in humans presenting different neurological disorders with a common expression of spasticity (57)(58)(59) or alterated upstream regulatory elements of the channels (26). Moreover, Ca V 1.3 calcium channels may increase neuronal excitabil-ity after injury indirectly, by cooperative gaiting of clustered Ca V 1.3 channels (60), activating calcium activated nonspecific cation channels (16) and BK channels (61) or promoting activation of calmodulin or calcium-dependent calpains to increase sodium channels activity after SCI (62,63). In our study nimodipine treatment does not completely block the sustained motor contraction in the chronic un-treated animals indicating that other cellular mechanisms than Ca V 1.3 channels support the the expression of spasticity.…”
Section: Discussionmentioning
confidence: 99%